Formation of Self-Assembled Mesophases During Lipid Digestion - Pham, Anna C.; Clulow, Andrew J.; Boyd, Ben J. (Frontiers in Cell and Developmental Biology, 2021)
Lipids play an important role in regulating bodily functions and providing a source of energy. Lipids enter the body primarily in the form of triglycerides in our diet. The gastrointestinal digestion of certain types of lipids has been shown to promote the self-assembly of lipid digestion products into highly ordered colloidal structures. The formation of these ordered colloidal structures, which often possess well-recognized liquid crystalline morphologies (or ‘mesophases’), is currently understood to impact the way nutrients are transported in the gut and absorbed. The formation of these liquid crystalline structures has also been of interest within the field of drug delivery, as it enables the encapsulation or solubilization of poorly water-soluble drugs in the aqueous environment of the gut enabling a means of absorption. This review summarizes the evidence for structure formation during the digestion of different lipid systems associated with foods, the techniques used to characterize them and provides areas of focus for advancing our understanding of this emerging field.